Perancangan Sistem Informasi Simpan Pinjam Pada Koperasi Wredatama Krakatau Steel (Kopwekas) - Darpi Darpi; Sawitri Nurhayati; Khasan Asrori (Teknik Informatika Fakultas Ilmu Komputer, 2021)
The management of savings and loans at the Wredatama Krakatau Steel Cooperative (Kopwekas) already uses Microsoft Excel, but in savings and loan transactions there are still obstacles, such as the process of recording deposits, loans and arrears of members. This requires accuracy in the checking process and waste of processing time.With these problems, this cooperative needs to use a savings and loan application that can assist in the processing of savings and loan data.The methodology used in the design of this information system is the Waterfall Method. This system is designed using the concepts of DFD (Data Flow Diagram) and ERD (Entity Relationship Diagram) and is implemented using the Microsoft Access 2019 Database, and Visual Basic 6.0.The expected result of this research is to produce a savings and loan information system that is equipped with processing customer deposits, and customer loans. By using this information system, data processing and report generation becomes easier, faster with accurate data